Nos embalos de shows musicais: uma proposição de escalas de satisfação com o show, socialização entre os frequentadores de shows e identificação com a música - Pires, Lúmia Massa Garcia (2016)
This research focused on proposing and validating three different measuring instruments related to concerts’ attendees: scale of satisfaction of concerts' attendees, scale of socialization in concerts and scale of identification with music. According to Cole and Chancellor (2009), different attributes of a music festival generate different impacts on attendees, that can also be considered for the context of concerts. However, at the moment, researches in the field of Administration, about this issue, are still recent (GETZ, 2010). Thus, this study is justified and supported on the following points: (a) to increase knowledge of consumer behavior which attend concerts, (b) because it is an exploratory study and, at the moment, pioneer, especially with regard to the Brazilian Academy; (c) the lack of information on key aspects which influence satisfaction, socialization and identification with music considering concerts' attendees; (d) the lack of measuring instruments (scales) related to these constructs; (e) the managerial relevance, once the concert is the main source of income for many professionals in the music industry (SALAZAR, 2010), they can use part of the information of this work to formulate new strategies to plan and organize concerts. Considering this scenario, it was selected three different constructs to study: the satisfaction of the concerts' attendees, socialization among them and identification with music. To reach the goal of this research, it was applied a qualiquantitative method. Firstly, it was developed the qualitative phase using focus groups in order to identify the key aspects which influence the satisfaction, socialization and identification with the music in the context of concerts' attendees. Among the main results of the qualitative study, when it comes to satisfaction of the concerts' attendees, the most significant factors reported by the respondents were related to services - especially for beverage supply, cleaning of bathrooms and lines that form at the event - organization, concert infrastructure and artists' performance. Moreover, considering the socialization among concerts' attendees context, it was found that most respondents usually go to this kind of event with other people, but some did not exclude the possibility to attend alone. About identification with music, it was revealed that music is very important for someones as they would consider the possibility of going to a concert, even alone, since they could sing most of the songs of the setlist chosen by the artist. The quantitative phase was developed in order to propose and validate the three measure instruments targeted. In this second phase, six steps were followed for the construction of the proposed measurement scales, according to Vieira (2011): (a) defining the constructs; (b) preparation of the items of the constructs; (c) items content validation; (d) application of the items in pre-test research; (e) application of the scales in official study; (f) conducting construct validity studies. In the official study phase, an online survey was published on social networks requiring respondents to answer a set of questions about the last concert that he or she has participated in the last 12 months and, as a result, 314 valid responses were obtained. Regarding the results of the quantitative study, the three scales - scale of satisfaction of concerts' attendees, scale of socialization in concerts and scale of identification with music - have been proposed and validated statistically. After the end of the process, the scale of satisfaction of concerts' attendees was configured with 19 items measured in Likert scale of 7 points, and divided into three factors: Satisfaction regarding the Core Business (Alpha = 0,907 and 6 items); Satisfaction regarding Organization and Infrastructure (Alpha = 0,869 and 7 items); and Satisfaction regarding Secondary Services (Alpha = 0,882 and 6 items). The socialization in concerts scale was configured as a one-dimensional instrument, containing three indicators measured in Likert scale of 7 points (Alpha = 0.882). Finally, the identification with music scale was configured of 7 indicators, measured in Likert scale of 7 points, and divided into two factors: Passive Identification with Music (Alpha = 0,933 and 5 items); Active Identification with Music (Alpha = 0,625 and 2 items). Therefore, it can be stated that the overall objective of this study was achieved.